ANALISIS PERILAKU BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DI SMP - Ibrahim, Muhammad Maulana; Khosmas, F.Y.; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to find out on students’ behavior in learning Social Studies subjects in class VII Pontianak 10 Public Middle School. The research method is usedthe descriptive, with a form qualitative research. Resources of the data in this study were VII grade students. Thedata were observation, documentation and the results of interviews with class VII students. The results of the study showed that the learning behavior carried out by class VII students were not good, because there were still students who behaved improperly such as daydreaming, chatting, going out of class, not taking notes, and not listening to the teacher when the learning process was good. However, from several aspects that have been examined in student skills there were some categorized as good enough but there were also students’ skill that cannot be categorized as good, namely reading skills, students lack the desire to read known from their lack of knowledge. Keywords: Learning Behavior, on Students